The Influence of Board Gender Diversity, Board Size, Return on Assets, Leverage, And Current Ratio on Forward-Looking Information Disclosures - Varian, Muhammad Davin Yuan; Puspawati, Dewita; Kurniawan, Firdaus (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of Board Gender Diversity (BGD), Board Size, Return on Assets (ROA), Leverage, and Current Ratio on Forward-Looking Information Disclosures (FLID) in LQ45 companies listed on the Indonesia Stock Exchange (IDX) that published annual reports from 2020 to 2021. The sample consists of 90 companies over the 2020–2021 period. Based on predetermined criteria and using purposive sampling, a total of 82 companies were selected for analysis. The data were processed using multiple regression analysis with the assistance of SPSS. The results of the study show that: (1) Board Gender Diversity (BGD) has a significant influence on Forward-Looking Information Disclosure; (2) Board of Directors (BOD) does not have a significant influence on Forward-Looking Information Disclosure; (3) Return on Assets (ROA) does not have a significant influence on Forward-Looking Information Disclosure; (4) Leverage does not have a significant influence on Forward-Looking Information Disclosure, indicating that the company’s debt level is not a major consideration in disclosing forward-looking information; and (5) Current Ratio (CR) has a significant influence on Forward-Looking Information Disclosure.